Elite female soccer players' dual career plans and the demands they encounter. Issue 1 (2nd January 2022) - Harrison, Grace E.; Vickers, Emma; Fletcher, David; Taylor, Guy
Abstract: An increasing number of female soccer players are playing at the elite level. It is important to encourage these players to remain mindful of the benefits of carrying out a dual career (e.g., higher education and elite sport path). The current study provides an investigation of players' dual career plans and the demands they encounter. The guiding framework used within the research was the Push–Pull theoretical framework. Semistructured interviews were conducted with 11 participants, encapsulating a variety of players at differing stages of their academic/vocational development. The data were analyzed using thematic analysis. All but 1 player in compulsory and secondary education were found to have a desire to carry out higher education, with 3 of these players planning to attend university in America. The main reason given by players for planning to continue education was to "have something to fall back on." Dual career difficulty was found to increase as players' level of education increased (i.e., from school to university and from university to vocation). Suitable support systems (e.g., university support, family support) were found to play an integral role in the dual career demands faced by participants, with players receiving varying levels of support from their educational institutions and soccer clubs. This article advances previous work on the dual careers of athletes, focusing specifically on English women's soccer during a period of key change within the governing body. Lay summary : We explored the decisions of and demands faced by female soccer players as they strive to combine work/education with their sporting commitments during a time of a change within The Football Association. Female soccer players were found to experience differing levels of support from their educational provider and soccer clubs.